Detection of depressive-anxiety symptomatology and associated risk factors among pregnant women in a low-income neighborhood. (2nd October 2021) - Gomà, Marta; Martínez, Maria; Blancafort, Xavier; Muniente, Gloria; Antón, Silvia; Lara, Silvia; Arias-Pujol, Eulàlia; Llairó, Antònia; Nanzer, Nathalie
Abstract: Aim: To determine the prevalence of anxiety-depressive symptomatology and associated risk factors in a population of pregnant women in the low-income neighborhood of Roquetes (Barcelona, Spain). Design: Quasi-experimental, cross-sectional study. Location: The study was carried out at the Primary Care Center, Roquetes Canteres, Barcelona. Participants: Between 2015 and 2017, all pregnant women who visited the Sexual and Reproductive Care Team in Primary Care (ASSIR) or their Family Physician (FP) were invited to take part in a study if they met the following criteria: (a) over 18 years old (b) able to understand in any of the 4 study languages. Of a total of 239 gestating women, 19 declined to participate, 14 moved away from the area and 16 underwent voluntary termination of pregnancy, leaving a sample of 190 subjects. Material and methods: The Edinburgh Postnatal Depression Scale (EPDS) was used to detect depressive symptomatology, the State-Trait Anxiety Inventory (STAI) was used to assess anxiety, and a sociodemographic data questionnaire was administered. Once all descriptive demographic data from the whole sample was analyzed, baseline clinical and demographic characteristics were compared using the independent t-test for continuous variables and the chi-squared analysis for categorical variables. Results: The t-test showed that 48% of pregnant women presented an at-risk degree of anxiety-depressive symptomatology, double that found in the general population. Applying a chi-squared test to the at-risk and non-risk groups revealed associated prenatal risk factors including: having a history of violence; living in a rented room, mistreatment in infancy and mental health issues. The ROC curves analysis obtained a cutoff point score of 4 Accumulated Associated Factors (AAF) (AUC 0.765, p < .001, 57% sensitivity and 79% specificity). Conclusions: Our study shows that rates of anxiety-depressive symptomatology in a population with considerable socio-economic deprivation can more than double. AAF in the population at risk of anxiety and depression were detected, highlighting the need to allocate resources to identification and prevention during pregnancy. This requires the involvement of a multidisciplinary, professional team with a biopsychosocial perspective.